Hemorrhagic pneumonia and upper lobe pulmonary cavitary lesion caused by Streptococcus pyogenes. Issue 2 (4th March 2021) - Nair, Gayatri B; Gopalakrishna, Harish; Conti, Ricardo
ABSTRACT: A 33-year-old previously healthy man from Mexico who presented with massive hemoptysis, fevers, chills and found to have cavitary lesions in the right upper lobe of lung was highly suspicious for tuberculosis. The patient was treated with vancomycin, ceftriaxone, azithromycin and placed on isolation for suspected tuberculosis. Sputum AFB stains were negative and blood cultures grew Group A Streptococcus [GAS]. Antibiotics were narrowed down to ampicillin-sulbactam and the patient was discharged with significant clinical improvement. Strep A pyogenes is a rare cause of cavitary hemorrhagic pneumonia but is associated with high mortality. Clinical suspicion and early diagnosis are crucial in saving the patient.